Optical measurement of the alteration kinetics of porous building materials during salt crystallization - Gonçalves, T. D. (2014)
In salt crystallization tests, porous building materials are typically subjected to extreme conditions, such as high temperatures or successive wet/dry cycles, in order to obtain measurable changes within a reasonable period of time. However, the unrealistic testing conditions may distort the results. This can be particularly significant for salts such as sodium sulfate, which can give rise to massive contact- or temperature-induced crystallization processes that hardly occur in the architectural heritage. Here, we propose a new method where the small changes undergone by the porous material are measured by a non-contact optical technique at the micrometer scale. This allows using test conditions more representative of those that generally occur on site. Topographic profiles are obtained during the process, from which an alteration kinetics curve is afterwards calculated [1]. The alteration curve can be combined and compared to the drying kinetics curve since the system, due to a recent update, permits simultaneous gravimetric measurements [2]. It also allows carrying out time-lapse photography, which may provide animations of the macroscopic alteration process. We report, as an example, sodium sulfate crystallization tests consisting of a single isothermal drying event at 20ºC and 50% RH. The tests were performed on natural stones, relevant for the architectural heritage, which developed either delamination or simply efflorescence. Both types of alteration were successfully characterized by the above described method. The results show that, under the chosen conditions, sodium sulfate can develop decay patterns similar to those frequently observed on site. The proposed method opens new perspectives for the development of salt crystallization tests that are more appropriate than those currently available to study decay processes and to evaluate materials and treatments for the architectural heritage